Methodology for investigation of stone dust combustion and detonation processes in mining - Vladimir A. Rodionov; Zaur A. Abiev; Sergey Ya. Zhikharev (Perm Journal of Petroleum and Mining Engineering, 2018)
The paper presents results of the study of processes of coal dust detonation combustion obtained using a technique approved by the authors. The essence of the technique is the use of a specific coal dust fraction to study the explosion pressure, explosion pressure increase rate and transformation coefficient. It allows applying the results of a laboratory experiment to the actual data of explosion and combustion of dust and gas mixtures of mines that have a much larger volume. In other words it allows predicting the explosion pressure increase rate in relation to specific excavation of coal mines. The methodology for studying combustion and detonation processes, briefly described in the article, is based both on requirements of modern regulatory documents and the practical experience of research institutes engaged in similar research. The practical component of the method is based on an installation which represents an explosive combustion chamber in the form of a sphere with a volume of 20 liters. The data of detonation combustion are processed using application software and presented graphically in three figures. It is shown that dispersion composition of coal dust indluences on the explosion pressure, explosion pressure increase rate and transformation coefficient. Research work is carried out with a sample of coal of KS-type from a thick beam of the mine named after Dzerzhinskiy. As a result of the analysis of digital and graphic data obtained during processing, it is proved that dust with fractional composition of 63-94 μm is the most explosive. It is revealed that explosion pressure increase rate changes as a function of dust concentration in the installation reaction volume in the way that there was two maxima of the explosion pressure increase rate where one was at 100 g/m3 and the second at 400 g/m3. The results obtained during determination of the explosion pressure increase rate have shown the necessity of a non-trivial, more thoroughtful approach to study explosion pressure increase and, consequently, determin the transformation coefficient. In addition, analysis of the experimental data presented in the article confirmed that during the development of means of flame retardation and explosion suppression used in automatic means for explosion localization it is necessary to carry out further investigations with the coal dust fraction equal to 63-94 μm. The results obtained in the work will allow starting the study of the processes of detonation combustion in a dusty air containing methane.